2019
DOI: 10.1002/cl2.1038
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: Communication skills training for improving the communicative abilities of student social workers: A systematic review

Abstract: BACKGROUND 1.1 | The problem Good communication is central to social work practice (Koprowska, 2014; Lishman, 2009), underpinning the success of a wide range of social work activities. People in receipt of social work services value social workers who are warm, empathic, respectful, good at listening

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Advantages of using this framework include its focus on possible different levels of evaluation and its compatibility with various approaches used within communication skills training in social work education. The theoretical underpinnings of the effects of the intervention were outlined in the study protocol (Reith-Hall and Montgomery, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages of using this framework include its focus on possible different levels of evaluation and its compatibility with various approaches used within communication skills training in social work education. The theoretical underpinnings of the effects of the intervention were outlined in the study protocol (Reith-Hall and Montgomery, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Originally produced for the Campbell Collaboration Library, where the review is registered and the accompanying protocol can be found (Reith-Hall & Montgomery, 2019), this systematic review followed the Cochrane Handbook of Systematic Reviews for Interventions (Higgins, Thomas, Chandler, Cumpston, Page & Welch, 2021) and the PRISMA reporting guidelines (Page, McKenzie, Bossuyt, Boutron, Hoffmann, Mulrow et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…To address the first gap within the literature — the outcomes evidence — a systematic review aimed at investigating whether or not the teaching and learning of communication skills is effective has recently been undertaken [ 12 , 13 ]. Notwithstanding significant methodological challenges, there was overall consistency in the direction of mean change for the development of communication skills of social work students following training [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are expository (passive) methods, which take into account primarily the processes of teaching, with the teacher in their center and an example being a lecture. Therefore, our experiment, conducted online after the COVID-19 lockdown regulations were announced, used active methods based on group collaboration such as simulating conversations with customers, modeling correct behavior, and providing feedback [18].…”
Section: Introductionmentioning
confidence: 99%